THE INFLUENCE OF INNOVATION AND PROMOTION ON CONSUMER PURCHASE DECISIONS ON PANGSIT MIE PALU - Sianto, Fifi Marcella; Thehumury, Christine Febrilia; Holiwono, Marchel Rocky; Putra, Sinar (Review of Management and Entrepreneurship, 2023)
Developments in the culinary business continue to increase. Seeing this makes competition between businesses even tighter, so that every culinary business needs to compete to get consumers so that its business can continue to survive. Attracting the attention of consumers can encourage consumers to become loyal to the products offered by a business. This study aims to know the effect of innovation and promotion on consumer purchasing decisions on Pangsit Mie Palu. This data using a descriptive research method. The distribution of questionnaires was used in this study to obtain data related to innovation, promotion, and purchasing decisions in this study. There were 103 consumers of Mie Pangsit Palu in the city of Makassar. Statistical Product and Service Solution (SPSS) was used to managing the obtain data through multiple linear regression analysis, the results of the T test, and the F test. Through the results of the data processing, it was found that (1) culinary product innovation has a significant and positive influence on purchasing decisions on Pangsit Mie Palu; (2) promotions have a significant and positive influence on purchasing decisions on Pangsit Mie Palu; (3) innovation and promotion have a significant influence on purchasing decisions of Pangsit Mie Palu.